2010
DOI: 10.1007/s11418-010-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of isoflavones and saponins in Pueraria flowers using HPLC coupled to an evaporative light scattering detector and isolation of a new isoflavone diglucoside

Abstract: The Pueraria flowers, Puerariae Flos [Puerariae Lobatae Flos (the flowers of P. lobata) and Puerariae Thomsonii Flos (the flowers of P. thomsonii)], have been used as crude drugs to counteract the overconsumption of alcohol in Japan and China. Both types of Puerariae Flos contain a large amount of isoflavones and saponins. Simultaneous analysis of the total saponin and isoflavone fraction within the flowers has proven difficult thus far; however, profile analysis of saponin and isoflavone levels was attempted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The result was in agreement with the previous reports [38], which showed that the B-ring substitution pattern of flavones is a significant structural feature for their function. All of the 13 compounds identified in P. lobata flower were all proven bioactive compounds [39][40][41]. Therefore, it is believed that this proposed analytical method could be applied in screening bioactive compounds in TCMs.…”
Section: Interaction Of Bioactive Compounds From P Lobata Flower Witmentioning
confidence: 93%
“…The result was in agreement with the previous reports [38], which showed that the B-ring substitution pattern of flavones is a significant structural feature for their function. All of the 13 compounds identified in P. lobata flower were all proven bioactive compounds [39][40][41]. Therefore, it is believed that this proposed analytical method could be applied in screening bioactive compounds in TCMs.…”
Section: Interaction Of Bioactive Compounds From P Lobata Flower Witmentioning
confidence: 93%
“…Other used reference compounds were isolated from the extracts of the flowers of P. lobata and P. thomsonii in our previous studies. 9,10,13,27) They included 6-hydroxygenistein-6, 7-di-Oglucoside (2), 6-hydroxygenistein-7-O-glucoside (7), rutin (8), tectorigenin-7-O-xylosylglucoside (10), genistin (11), tectoridin (12), 6-hydroxybiochanin A-6, 7-di-O-glucoside (13), gehuain (14), glycitein (17), kakkalide (20), genistein (22), tectorigenin (25), biochanin A (27), astragaloside VIII (28), soyasaponin I (29), irisolidone (30), soyasaponin IV (31), kaikasaponin III (32), kaikasaponin II (33), kaikasaponin I (34), kakkasaponin I (35), azukisaponin I (36), baptisiasaponin I (37), phaseoside IV (38), kakkasaponin II (39) and kakkasaponin III (41). The identity of these compounds were confirmed by melting point, UV, IR, 1 H-and 13 C-NMR and MS, and their purities evaluated with HPLC-photodiode array detector (PDA) were more than 95%.…”
Section: Methodsmentioning
confidence: 99%
“…For example, tectoridin shows potent effects on the inhibition of prostaglandin E 2 (PGE 2 ) production, while kakkalide has no significant effect. 17) Actually, Flos Puerariae Lobatae and Flos Puerariae Thomsonii have been indiscriminate in clinical use and in the preparation of phytopharmaceuticals, which is a serious issue in relation to the efficacy, quality control and safety.…”
mentioning
confidence: 99%
“…Tectoridin (1) and tectorigenin (2) were isolated from flowers of P. thomsonii Benth [15], and Te-7G (3), Te-7S (4), and Te-4 S (5) were isolated from urine of rats orally administered tectoridin [14]. The identity of these compounds was confirmed by spectoral analysis including UV, infrared radiation (IR), 1 H and 13 C NMR, and mass spectrometries (MS).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%